Personal Growth, Social Change or Human Capital: A document analysis of an online education program for adult learners - Nakita Dolet; Maeghen L MacDonald (Adult Education Research Conference, 2016)
This document analysis interrogates how one institution balances classically competing objectives of emancipatory learning, personal growth, and human resource development in an online adult education program.
Keywords: online education; transformative learning; human capital; adult education